2022
DOI: 10.1097/npt.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Coaching via Telehealth for People With Parkinson Disease: A Cohort Study

Abstract: Background and Purpose: Physical activity (PA) has many known benefits for people with Parkinson disease (PD); however, many people do not meet recommended levels of frequency or intensity. We designed Engage-PD, a PA coaching program delivered via telehealth and grounded in self-determination theory to promote PA uptake and facilitate exercise self-efficacy in people with Parkinson disease. This study aimed to determine the feasibility and preliminary efficacy of Engage-PD, and to explore whether baseline cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Obtaining survey data prior to the virtual visit allows therapists to be more efficient with interview time, by developing focused, personalized discussion points. Although many physical therapy interventions for PwP are amenable to telehealth, development of an individualized multimodal intervention plan requires a comprehensive examination battery to facilitate clinical decision making, design the plan of care, and evaluate patient progress (Flynn et al, 2023;Osborne et al, 2022;Quinn et al, 2020;Shih et al, 2022;van der Kolk et al, 2019). One of the primary concerns in telehealth is safety of administering tests and measures when a therapist is not in person to provide guarding and environmental cueing (Bennell et al, 2021;Bianchini et al, 2022;Colón-Semenza et al, 2023;Cubo et al, 2021;Thwaites et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining survey data prior to the virtual visit allows therapists to be more efficient with interview time, by developing focused, personalized discussion points. Although many physical therapy interventions for PwP are amenable to telehealth, development of an individualized multimodal intervention plan requires a comprehensive examination battery to facilitate clinical decision making, design the plan of care, and evaluate patient progress (Flynn et al, 2023;Osborne et al, 2022;Quinn et al, 2020;Shih et al, 2022;van der Kolk et al, 2019). One of the primary concerns in telehealth is safety of administering tests and measures when a therapist is not in person to provide guarding and environmental cueing (Bennell et al, 2021;Bianchini et al, 2022;Colón-Semenza et al, 2023;Cubo et al, 2021;Thwaites et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have supported the feasibility and efficacy of telehealth-delivered interventions for PwP ( Shih et al, 2022 ; Vellata et al, 2021 ). While researchers have used a range of outcome assessments in these studies, there has not been a structured approach to conducting physical therapy assessments via telehealth for PwP.…”
mentioning
confidence: 99%
“…Based upon data from a review of 10 randomized control trials, Ortega-Hombradros ( 19 ) concluded that combined resistance and aerobic exercise programs should be completed at a moderate intensity, 2x/week to maximize benefits and reduce risk of worsening fatigue. Effective telehealth multimodal telerehabilitation exercise programs have been described in the Parkinson’s ( 20 ) and Duchenne muscular dystrophy ( 21 ) populations.…”
Section: Specific Exercises and Adaptability To Telehealthmentioning
confidence: 99%